Pharmaceutical Potentials and Formulation Perspectives of Corallocarpus Epigaeus: A Compehensive Review - M.L. Indhumathi; M. Mumtaj Begum; Dr. B. Premkumar; E. AnbuSelvam; S. Swathi; Anand Kumar Singh; Muhammed Nihal; B. Vaishnav (Asian Journal of Pharmaceutical Research and Development, 2025)
Corallocarpusepigaeus, popularly referred to as Akasa Garudan Kizhangu, is a lesser-known but important medicinal plant from the Cucurbitaceae family. In Siddha medicine and local healing traditions, the tuber has long been valued for treating digestive discomfort, reducing swelling, and clearing toxin-related ailments. Scientific investigations have revealed that the plant contains several biologically active groups of chemicals, including cucurbitacins, flavonoids, triterpenoids, alkaloids, and various glycosides. These compounds contribute to the plant’s antioxidant effects and its ability to fight inflammation, microbes, and liver-related issues. Although traditional practices highlight its therapeutic value, modern pharmaceutical research on C. epigaeus is still in its early stages. Only limited studies are available on how to extract its active molecules efficiently, how the plant behaves during preformulation and stability testing, or how to convert it into reliable dosage forms. Because of these gaps, the development of standardized herbal medicines from this plant remains a challenge. This review brings together the currently available information on the plant’s botanical features, chemical composition, and biological activities. It also outlines the formulation difficulties that must be addressed. Future research may benefit from exploring advanced nano–drug delivery technologies—such as nanoemulsions, nanosponges, and phytosomes—which can improve solubility, stability, and site-specific delivery of the plant’s active constituents. Stronger collaboration between traditional medicine, phytochemistry, and pharmaceutical sciences could help transform Corallocarpusepigaeus into a dependable herbal therapeutic.